2017
DOI: 10.1097/ccm.0000000000002260
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Utilization of Life Support and End-of-Life Care for Medical ICU Patients With Versus Without Cancer

Abstract: Among patients dying in the medical ICU, the diagnosis of active cancer influences the intensity of life support utilization and the quality of end-of-life care. Patients with active cancer use less life support and may receive better end-of-life care than similar patients without cancer. These differences are likely due to biases or misunderstandings about the trajectory of advanced nonmalignant disease among patients, families, and perhaps providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
3
0
9
Order By: Relevance
“…It has been shown before that the diagnosis of cancer influences end-of-life care, with cancer patients receiving, generally, less aggressive care and better quality of end-of-life care. ( 5 , 30 , 31 ) It has been hypothesized that some of this difference may be due to misunderstandings about the trajectory of the disease or lack of familiarity with PC by the providers. ( 31 ) It is possible that the implementation of the program had a greater effect in this more vulnerable population of non-cancer patients, as cancer patients may have already been receiving more appropriate end-of-life care, even though this correlation should be carefully examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown before that the diagnosis of cancer influences end-of-life care, with cancer patients receiving, generally, less aggressive care and better quality of end-of-life care. ( 5 , 30 , 31 ) It has been hypothesized that some of this difference may be due to misunderstandings about the trajectory of the disease or lack of familiarity with PC by the providers. ( 31 ) It is possible that the implementation of the program had a greater effect in this more vulnerable population of non-cancer patients, as cancer patients may have already been receiving more appropriate end-of-life care, even though this correlation should be carefully examined.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à caracterização dos estudos, quanto ao desenho metodológico, 38 eram de abordagem quantitativa (Årestedt et al, 2018;Axelsson et al, 2018;Beauverd et al, 2014;Bedell et al, 1986;Camhi et al, 2009;Chang & Brass, 2014;H.-C. Chou et al, 2018;Clarke et al, 2014;Cook et al, 1995;Courtwright et al, 2015;DeMartino et al, 2017;Economos et al, 2019;Farrington et al, 2014;Fu et al, 2018;Gilbar et al, 2019;Hamano et al, 2018;Hiramoto et al, 2019;Koff et al, 2017;Liu et al, 2015;Moffat et al, 2016;Montagnini et al, 2018;Mori et al, 2019;Mroueh et al, 2019;Opstelten et al, 2017;Parpa et al, 2010;Penders et al, 2020;Penrod et al, 2012;Piili et al, 2018;Pugh et al, 2009;Seale, 2010;Steindal et al, 2015;Syed et al, 2017;Taniguchi et al, 2016;Thomas et al, 2014;Tsai et al, 2018;Verhofstede et al, 2017;Wang et al, 2019;Ziegler et al, 2018), 13 qualitativa (Bélanger et al, 2014;W.-Y. S. Chou et al, 2017;De Bal et al, 2006;De W...…”
Section: Resultsunclassified
“…O período de publicação dos estudos variou entre 1986 e 2020, sendo os anos com maior publicação 2017 (W.-Y. S. Chou et al, 2017;De Bal et al, 2006;De Witt Jansen et al, 2017;DeMartino et al, 2017;Guardia-Mancilla et al, 2017;Koff et al, 2017;Kruser et al, 2017;Opstelten et al, 2017;L. Robijn et al, 2017;Sellars et al, 2017;Syed et al, 2017;Verhofstede et al, 2017;Wagemans et al, 2017), 2018 (Årestedt et al, 2018;Axelsson et al, 2018;H.-C. Chou et al, 2018;Fu et al, 2018;Hamano et al, 2018;Montagnini et al, 2018;Piili et al, 2018;Lenzo Robijn et al, 2018;Scott et al, 2018;Tsai et al, 2018;Ziegler et al, 2018(Díez-Manglano et al, 2019Economos et al, 2019;Gilbar et al, 2019;Hiramoto et al, 2019;Mori et al, 2019;Mroueh et al, 2019;Wang et al, 2019), respectivamente.…”
Section: Resultsunclassified
“…In a French survey interviewing physicians and nurses, there was a strong resistance to terminal extubation, particularly among nursing professionals [16]. It was found that end-of-life patients with non-cancer diseases (particularly chronic respiratory diseases and post-cardiac arrest neurological sequelae) have a longer mechanical ventilation time, more dialysis performed, and longer ICU stay than patients with cancer, and they receive lower quality palliative care [12,24]. In our study, with only 25% of patients with ELM-PC having cancer, this quality-ofassistance gap of palliative care with more adequate end-of-life care for cancer patients was also seen, although the number of patients was very low.…”
Section: Discussionmentioning
confidence: 99%